Diversity and abundance of mosquitoes (Diptera: Culicidae) in Universiti Malaysia Sabah Campus, Kota Kinabalu, Sabah, Malaysia - Nurhayati Hassan,; Dawood, Mahadimenakbar Mohamed (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
A study on the abundance and diversity of mosquitoes (Diptera: Culicidae) was carried out in University Malaysia Sabah (UMS). The study was conducted (i) to observe the diversity of mosquitoes in UMS, (ii) to compare the abundance of mosquitoes in study sites, (iii) to observe the interactions of abiotic factors such as time and temperature and (iv) to observe the mosquitoes’ breeding sites. The samplings were done for 16 days for indoor and outdoor by using bare leg capture method and were done for 12 hours on every sampling day. Temperature was recorded every hour within 1800 until 0600. A total of four genera and 11 species of mosquitoes were recorded from the samplings. The highest abundance recorded were Culex annulirostris, Culex sitiens, Culex pipiens, Culex tritaeniorhynchus and Aedes albopictus. Hostel A-B recorded seven species, Hostel C-D recorded six species, Hostel E recorded six species, library’s cafe recorded six species and library’s lake recorded seven species. The dominant species at each study site were Culex annulirostris, Culex sitiens, Culex pipiens and Culex tritaeniorhynchus.